A Clinician's Approach to Peripheral Neuropathy - Siao, Peter; Kaku, Michelle (Seminars in Neurology, 2019)
Peripheral neuropathies are a group of disorders that affect the peripheral nervous system, for which hundreds of etiologies have been identified. This article presents a stepwise approach to the evaluation and workup of peripheral neuropathy, which starts with a detailed history of symptoms, family and occupational history, and a neurological as well as general physical exam. Pattern recognition of various neuropathies can help to build a differential diagnosis based on the presentation. Such patterns include acute versus chronic, primary demyelinating versus axonal, hereditary versus acquired, asymmetric versus symmetric, presence of facial palsies, sensory or motor predominant, and presence of prominent autonomic symptoms. Early categorization of the type of neuropathy can help focus the workup for peripheral neuropathy. Nerve conduction studies and electromyography (NCS/EMG) is the primary diagnostic tool in the evaluation of patients with large-fiber polyneuropathy. One of the most important roles of NCS/EMG is to help categorize polyneuropathy as primary axonal versus primary demyelinating. The finding of a primary demyelinating polyneuropathy narrows the differential diagnosis of polyneuropathy dramatically and increases the chances of finding a treatable etiology. Laboratory workup includes serum studies and potentially cerebrospinal fluid, genetic studies, immunological markers, and fat pad biopsy for select patients. Skin biopsy may be used to assess intraepidermal nerve fiber density if small-fiber neuropathy is suspected, and nerve biopsy may be useful in select cases. In recent years, magnetic resonance imaging and neuromuscular ultrasound have also shown promise in the evaluation of peripheral neuropathy. Identification of the etiology of neuropathy is crucial and often time-sensitive, as an increasing number of causes are now reversible or treatable.
Keywords: peripheral neuropathy; polyneuropathy; diagnosis; clinical; neurophysiologic